2012
DOI: 10.1345/aph.1r158
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Nephrotoxicity to Vancomycin Trough Serum Concentrations in a Veteran's Population: A Retrospective Analysis

Abstract: In the population evaluated, hypotension and trough concentrations were predictors of nephrotoxicity; elevated vancomycin trough concentration had the highest odds of association. These data reinforce the close therapeutic monitoring guidelines for vancomycin trough concentrations, especially when targeting troughs of 15-20 mg/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 15 publications
1
67
1
Order By: Relevance
“…Although it has been difficult to demonstrate a direct renal injury attributed to vancomycin when given in lower doses in the past, there is consistent evidence that aggressive dosing aimed at curbing the trend of reducing microbial sensitivity is associated with higher incidence of AKI [Hanrahan et al 2015;Elyasi et al 2012;Horey et al 2012;Cano et al 2012]. In a review of the literature by Elyasi and colleagues, vancomycin renal toxicity had a range of 10-20% in patients using conventional doses while the range was 30-40% for those treated with higher doses (10-20 mg/l) [Elyasi et al 2012].…”
Section: Vancomycin Exposure: Higher Dosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been difficult to demonstrate a direct renal injury attributed to vancomycin when given in lower doses in the past, there is consistent evidence that aggressive dosing aimed at curbing the trend of reducing microbial sensitivity is associated with higher incidence of AKI [Hanrahan et al 2015;Elyasi et al 2012;Horey et al 2012;Cano et al 2012]. In a review of the literature by Elyasi and colleagues, vancomycin renal toxicity had a range of 10-20% in patients using conventional doses while the range was 30-40% for those treated with higher doses (10-20 mg/l) [Elyasi et al 2012].…”
Section: Vancomycin Exposure: Higher Dosesmentioning
confidence: 99%
“…The plasma trough level of vancomycin was a major correlate of nephrotoxicity [Hanrahan et al 2015]. Implying a causal association, there is also a linear relationship between higher events of AKI and a graded plasma trough concentrations [Horey et al 2012]. Thus there was 3.1%, 10.6%, 23.6% and 81.8% incidence of AKI for those with trough levels of 10-15, 15-20, 20-35 and greater than 35 mg/l, respectively [Horey et al 2012].…”
Section: Vancomycin Exposure: Higher Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…An established link exists between vancomycin levels and renal toxicity, with van Hal et al among others showing that if the vancomycin trough is >20 mg/L toxicity is 33%, and if it is <20 mg/L then toxicity is 20%, so levels ought to be measured [28,64]. A recent meta-analysis by van Hal et al showed an increased probability of a nephrotoxic event not only with increasing trough concentrations but also length of exposure [28].…”
Section: Heteroresistancementioning
confidence: 99%
“…In recent years, vancomycin dosing has escalated, driven by concerns of increasing treatment failure, thought to be the result of increasing vancomycin MICs (MIC creep) among S. aureus isolates (4)(5)(6). Consequently, this strategy may lead to increased rates of nephrotoxicity (7)(8)(9)(10). This risk appears to be highest for patients who are particularly vulnerable to acute kidney injury due to comorbidities such as preexisting renal disease, acute illness, hypoperfusion from sepsis, or concomitant nephrotoxic medication (10,11).…”
mentioning
confidence: 99%